2020
DOI: 10.1038/s41598-020-63507-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between radiocaesium in muscle and physicochemical fractions of radiocaesium in the stomach of wild boar

Abstract: After the accident at the TEPCO Fukushima Daiichi Nuclear Power Plant in 2011, it became important to study radiation dynamics, assess internal radiation exposure and specify factors affecting radionuclide variation in wildlife. Therefore, it is necessary to investigate which physicochemical fractions of radiocaesium ( 137 Cs) are absorbed from ingested material in species with high activity concentrations of 137 Cs, such as wild boar. This study analysed the physicochemical fractions of 137 cs in the stomach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Large amounts of radionuclides were released from the reactors at the time of the FDNPP accident 3 . Of these, concerns surrounding the long-term accumulation of cesium-137 ( 137 Cs) in wildlife have been raised due to its relatively long physical half-life (30 year) and high bioavailability (i.e., absorption and transfer rates), as its chemical characteristics are similar to those of the monovalent cation potassium 4 , 5 . A high proportion of the radiocaesium released exists in an ionic state immediately after deposition in the soil, and then, after physical and chemical changes in the soil following deposition, radiocaesium binds to soil particles over time and becomes less easily dissolvable 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large amounts of radionuclides were released from the reactors at the time of the FDNPP accident 3 . Of these, concerns surrounding the long-term accumulation of cesium-137 ( 137 Cs) in wildlife have been raised due to its relatively long physical half-life (30 year) and high bioavailability (i.e., absorption and transfer rates), as its chemical characteristics are similar to those of the monovalent cation potassium 4 , 5 . A high proportion of the radiocaesium released exists in an ionic state immediately after deposition in the soil, and then, after physical and chemical changes in the soil following deposition, radiocaesium binds to soil particles over time and becomes less easily dissolvable 6 .…”
Section: Introductionmentioning
confidence: 99%
“…A high proportion of the radiocaesium released exists in an ionic state immediately after deposition in the soil, and then, after physical and chemical changes in the soil following deposition, radiocaesium binds to soil particles over time and becomes less easily dissolvable 6 . Such a physicochemical fraction of radiocaesium in the environment can also affect radiocaesium intake in wildlife [e.g., 5 , 7 ]. After the FDNPP accident, numerous studies reported that 137 Cs was present in many wildlife species, and extensive studies have been conducted on 137 Cs dynamics in organisms distributed in and around Fukushima (e.g., insects 8 ; amphibians 9 ; fishes 10 12 ; birds 13 ; and mammals 14 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…In vertebrates, a common tendency of muscle to accumulate 137 Cs has been reported in many studies. Examples are cattle [ 56 , 57 ], wild boars [ 58 , 59 , 60 , 61 ], Japanese monkeys [ 62 , 63 ], and fishes [ 64 , 65 ]. Accumulation of 137 Cs has been reported in various field-collected insects, spiders, and other invertebrates [ 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ].…”
Section: Introductionmentioning
confidence: 99%
“…For Cs, I, and Sr radioisotopes, several studies on F v and F m were published for temperate climates 1 , 14 – 29 . A very few studies on Cs and I radioisotopes have been reported for the Indian subcontinent as well 30 – 37 .…”
Section: Introductionmentioning
confidence: 99%